A synopsis of the genus Berkleasmium with two new species and new records of Canalisporium caribense from Zingiberaceae in Thailand - Bussaban B. (2014)
The genus Berkleasmium is reviewed based on the literature and two new species are described from recent collections. A synopsis and key is provided to the 24 accepted species. The new species, B. nigroapicale and B. sutheppuiense are described from dead pseudostems of Amomum siamense, and a morphologically similar fungus, Canalisporium caribense, found on the same host species is also reported.